Measurement and control of particulate emissions from cattle feedlots in Kansas - Guo, Li (Kansas State University, 2011)
Emissions of particulate matter (PM) are an increasing concern for large open beef cattle feedlots. Research is needed to develop science-based information on PM emissions and abatement measures for mitigating those emissions. This research was conducted to (1) measure PM concentrations emitted from large cattle feedlots, (2) compare different samplers for measuring concentrations of PM with equivalent aerodynamic diameter of 10 µm or less (PM10), (3) evaluate the relative effectiveness of pen surface treatments in reducing PM10 emissions, and (4) predict PM control efficiency of vegetative barriers. Concentrations of PM with equivalent aerodynamic diameter of 2.5 µm or less (PM2.5), PM10, and total suspended particulates (TSP) upwind and downwind of two large cattle feedlots (KS1, KS2) in Kansas were measured with gravimetric samplers. The downwind and net concentrations generally decreased with increasing water content (WC) of the pen surface; for effective control of PM emissions from feedlots, it appears that pen surface WC should be at least 20% (wet basis). Three types of samplers for measuring PM10 concentrations in feedlots KS1 and KS2 were compared: Tapered Element Oscillating Microbalance™ (TEOM), high-volume (HV), and low-volume (LV) PM10 samplers. Measured PM10 concentration was generally largest with the TEOM PM10 sampler and smallest with the LV PM10 sampler. A laboratory apparatus was developed for measuring the PM10 emission potential of pen surfaces as affected by surface treatments. The apparatus was equipped with a simulated pen surface, mock cattle hooves that moved horizontally across the pen surface, and PM10 samplers that collected emitted PM10. Of the surface treatments evaluated, application of water (6.4 mm) and hay (723 g/m2) exhibited the greatest percentage reduction in PM10 emission potential (69% and 77%, respectively) compared with the untreated manure layer. Computational fluid dynamics (CFD) was applied to predict airflow and particle collection by a row of trees (2.2 m high × 1.6 m wide). Predicted particle collection efficiencies generally agreed with published data and ranged from less than 1% for 0.875-µm particles to approximately 32% for 15-µm particles.
Keywords: Particulate matter; Cattle feedlot; Particulate mass concentration; Particle size distribution; Numerical simulation; Particulate emission control; Engineering, Agricultural (0539)